Diminished Progression of Periapical Lesions with Zoledronic Acid in Ovariectomized Rats - Wayama, Marcelo Tadahiro; Yoshimura, Hitoshi; Ohba, Seigo; Yoshida, Hisato; Matsuda, Shinpei; Kobayashi, Junichi; Kobayashi, Motohiro; Gomes Filho, João Eduardo; Sano, Kazuo (Journal of endodontics, 2015)
The aim of this study was to investigate the effects of systemically administered zoledronic acid (ZOL) on the progression of periapical lesions in estrogen-deficient rats. Female Wistar rats were divided into the following groups: SHAM-veh, sham surgery treated with vehicle (physiological saline); OVX-veh, ovariectomy treated with vehicle; SHAM-ZOL, sham surgery treated with ZOL; and OVX-ZOL, ovariectomy treated with ZOL. Vehicle or ZOL was administered intravenously once a week for 4 weeks. The pulp of the mandibular first molar of all rats was exposed to the oral environment to induce a periapical lesion, and the lesions were analyzed after 7 and 30 days. The mandibles were examined by micro–computed tomographic imaging and histopathologic, histometric, and immunohistochemical analyses. Histopathologically, the OVX-veh group had more severe inflammation and bone loss and a larger number of cells that were positive for tartrate-resistant acid phosphatase compared with the SHAM-veh and OVX-ZOL groups; the SHAM-veh and OVX-ZOL groups were similar to each other. The SHAM-ZOL group had the lowest magnitude of these conditions. Tomographically, the OVX-veh group had greater bone loss than the other groups at both time points. The SHAM-veh, SHAM-ZOL, and OVX-ZOL groups had similar bone loss at both time points. In the sagittal section on day 30, the SHAM-ZOL group had lower bone loss compared with the SHAM-veh and OVX-ZOL groups. The hypoestrogenic condition aggravates the progression of periapical lesions. ZOL therapy may help contain bone destruction of periapical lesions. •The aim of this study was to investigate the effects of systemically administered zoledronic acid (ZOL) on the progression of periapical lesions in estrogen-deficient rats.•The hypoestrogenic condition aggravates the bone resorption associated with periapical lesion.•ZOL therapy may help contain bone destruction of periapical lesions.•The importance of dental disease to the pathogenesis of osteonecrosis must be emphasized, and this rat osteonecrosis model without tooth extraction can be used in further studies for exploring the relevant pathophysiological mechanisms.